A SPATIAL ANALYSIS OF THE IMPACT OF EDUCATION ON SOCIAL-ECONOMIC INEQUALITIES: A SPOTLIGHT ON ROMANIA - SIMIONESCU, Mihaela; CONSTANTIN, Daniela-Luminita (Theoretical and Empirical Researches in Urban Management, 2025)
This study examines the influence of higher education graduates, labour productivity, and public expenditure on the wage share of GDP in Romania in the 42 Romanian NUTS 3 regions in the 2014-2021 period using a dynamic panel data model. The wage share, calculated as employee compensation divided by GDP, serves as a proxy for income inequality, though it does not reveal individual wage distribution. However, the impact on income inequality remains unclear. Increased public spending, particularly on social programmes, translates to a lower wage share indicating reduced income inequality in Romania's specific case. The relation between labour productivity and wage share is not significant because of the public sector wage policies that prioritize catching up to private sector wages or inflation, rather than reflecting actual productivity gains. By strategically investing in education, reforming the public sector, and fostering a productive business environment, Romania can leverage its educated workforce and public spending to achieve a more equitable and prosperous future.